The effect of culturally responsive transformative teaching (CRTT) model in science learning on the environmental literacy ofseventh grade students - Septi Reggina Anggita Wijayanti; Riezky Maya Probosari; Icha Kurnia Wati; Muhammad Nur Hudha; Kadek Dwi Hendratma Gunawan; Lina Mahardiani; Nurma Yunita Indriyanti (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: Environmental damage in Indonesia is worsening, as shown by the low Environmental Performance Index and limited public awareness, which reflect low student environmental literacy. The Culturally Responsive Transformative Teaching (CRTT) model provides a contextual approach by integrating cultural values to enhance knowledge, attitudes, and pro-environmental behaviors.Aims and scope of paper: This study aims to determine the effect of the Culturally Responsive Transformative Teaching (CRTT) model on science learning on the environmental literacy of 7th grade students.Methods: This study used a quasi-experimental method with a pretest-posttest control group design. The sampling technique was selected using cluster random sampling. The research instrument was the MSELS instrument adapted from Mc.Beth and Volk (2009) in the form of multiple-choice tests and questionnaires tailored to the 7th grade science material on ecology and biodiversity. The research sample used class 7 H as the control class with a discovery learning model consisting of 32 students and class 7I as the experimental class with a CRTT model consisting of 31 students.Result: The results showed that the CRTT model in science learning had an effect on the environmental literacy of 7th grade students with a significance value of 0.000 (0.000< 0.05).Conclusion: The study concludes that the CRTT model effectively enhances students’ environmental literacy in science learning, highlighting the need for cultural integration and further research across diverse contexts.